The Use of Real Options in Assessing the Development of Small Energy in Russia - Morozko, Natalia; Morozko, Nina; Didenko, Valentina (International Journal of Energy Economics and Policy, 2020)
The spatial development of small energy in Russia at the present stage solves the problems of energy supply in remote and inaccessible regions of the country, which determines the relevance of the issues addressed. The aim of the study is to assess the development of small energy in the country based on the use of economic and mathematical methods. The study was conducted using long-term strategic planning tools, real options, and a binomial model. Based on PEST analysis, macroeconomic factors affecting the development of small energy have been identified. To assess the development of small energy, it is necessary to take into account many risks and uncertainty, which necessitates the use of flexible management decisions using the real options method. It was revealed that with the uncertainty of demand, but the possibility of growth in demand in the future, as is the case in small energy, it is advisable to use a real option - CALL. A practical example of quantifying the value of a real CALL option is considered. Keywords: small energy, real options, binomial model JEL Classifications: C4, G3, M2, O1, Q4 DOI: https://doi.org/10.32479/ijeep.9158